Factors affecting unmet need for contraception among currently married fecund young women in Bangladesh. (1st November 2016) - Islam, Ahmed Zohirul; Mostofa, Md. Golam; Islam, Mohammad Amirul
Abstract: Objectives: The aim of our study was to explore the factors associated with unmet need for contraception among currently married fecund women under age 25, in Bangladesh. Methods: This study utilised a cross-sectional data ( n = 4982) extracted from the Bangladesh Demographic and Health Survey (BDHS) 2011. Multinomial logistic regression was used to identify the determinants of unmet need for contraception among currently married fecund young women. Results: The unmet need for contraception was 17% and contraceptive prevalence was 54% in this young group. Total demand for contraception was 71% and the proportion of demand satisfied was 77%. The results suggest that region, place of residence, religion, husband's desire for children, visits of FP workers, decision-making power on child health care, reading about FP in newspaper/magazine and number of births in three years preceding the survey were significant predictors of unmet need for contraception. Conclusions: The BDHS of 2011 found that unmet need for contraception among currently married, fecund women under 25 years old is higher than the national level, and hence different or more intensive programme initiatives are required for them than for older women. The present study identifies important predictors of unmet need for contraception among fecund married Bangladeshi women under age 25.